Desain Ekstrakurikuler Al-Qur’an Di SMP Pertiwi Medan - Arlina Arlina; Rabiatul Adawiyah; Salsabila Syfa Siregar; Alfina Azisi Br Purba; Fadila Hasibuan (Jurnal Pendidikan, Bahasa dan Budaya, 2023)
Studying the Qur'an is an obligation for every Muslim, because the Qur'an is the main guideline for Muslims in worship and muamalah. Reading and writing the Qur'an is a lesson that must be taught to students, starting from the elementary school level to the high school level. One way is to hold an extracurricular reading of the Qur'an. This research was conducted to find out how the Al-Qur'an extracurricular design at SMP Pertiwi Medan and its relation to improving students' ability to read the Al-Qur'an. This was done to find out whether the Al-Qur'an extracurricular provision had a significant effect on improving the ability to read and memorize the Al-Qur'an in students who took part in the extracurricular activities at Pertiwi Middle School, Medan. The method used in this study is a qualitative descriptive method, in which the descriptive method is used to describe the conditions in the field as they are. Based on the research conducted, the extracurricular design at SMP Pertiwi Medan is good, with the right methods and real support from the school. So that students who take part in extracurricular activities are on average in the good category, in which in this category students are able to read or memorize the Al-Qur'an properly and in accordance with the rules of tajwid science, even though they are not fully good in terms of sound.